Beijinger in New York - Tsʻao, Kuei-lin 1947-; Wang, Ted. (San Francisco Cypress Book Company, 1993)
"Story of Wang Qiming, a poor musician who arrives with his wife in New York, full of hope for a new life. Numerous setbacks fail to discourage them, and it appears the American dream will become reality for them. But with their success comes tragedy, as their wealth comes at a high cost for their family life"--P. [4] of cover.
Translation of: Pei-ching jen tsai Niu-yüeh.
Keywords: Chinese Americans -- Fiction; Musicians -- Fiction; New York (N.Y.) -- Fiction